Child abuse and stress disorders [ - Olive, M. Foster; Collins, Christine E. [ (Christine Elaine)]; Levitt, Patt (New York : Chelsea House, 2007)
Explores the correlations between child abuse and stress disorders, and discusses the long-term effects of traumatic experiences on both children and adults
Description based on print version record
Includes bibliographical references (p 101-103) and index
Keywords: Stress (Physiology) -- Juvenile literature; Stress (Psychology) -- Juvenile literature; Stress in children -- Juvenile literature